2010
DOI: 10.1007/s12194-010-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

Skin shift and its effect on navigation accuracy in image-guided neurosurgery

Abstract: Neuronavigation systems have been developed for image-guided neurosurgery to aid in the accurate resection of malignant brain tumors. Therefore, the accuracy of the neuronavigation is important. However, many factors can reduce the navigation accuracy during surgery. Before craniotomy, the patient's head is secured to a head frame with head pins; this fixation may cause displacement of fiducial markers and reduce the accuracy. We term this phenomenon skin shift. In this study, the extent of skin shift and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…As the precision of anatomically accurate models improve, concerns expressed in Ramon et al (2006) that head models generated from supine MRI scans may lead to errors in EEG source localizations may be warranted, an effect that might add to the confounding effect of "skin shift" (Mitsui et al, 2011). Indeed, anatomically accurate models of current flows in the context of transcranial stimulation have shown that small errors in CSF thickness lead to significant changes in the resulting current flows (Datta et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As the precision of anatomically accurate models improve, concerns expressed in Ramon et al (2006) that head models generated from supine MRI scans may lead to errors in EEG source localizations may be warranted, an effect that might add to the confounding effect of "skin shift" (Mitsui et al, 2011). Indeed, anatomically accurate models of current flows in the context of transcranial stimulation have shown that small errors in CSF thickness lead to significant changes in the resulting current flows (Datta et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In neurosurgery, skin shifting is a problem when head pins are used [22]. The use of bone-anchored screw markers has been recommended for better accuracy [14].…”
Section: Discussionmentioning
confidence: 99%
“…This is a reasonable hypothesis, since it has previously been experimentally shown that skin mobility with respect to the skull bone can range from 1.3-13.1 mm, with a mean of 5.34 ± 2.65 mm under load 16 . Figure 2 illustrates two ways loads can be applied to the skin that would cause relative motion between the optical tracking rigid body and the patient's skull.…”
Section: Potential Error Due To Skin Mobilitymentioning
confidence: 55%